PREBIOTICS AND POSTBIOTICS IN DERMATOLOGY AND COSMETOLOGY: A NARRATIVE REVIEW OF THEIR ROLE IN SKIN MICROBIOME RESTORATION AND INFLAMMATION MODULATION - Karolina Szałata; Monika Czekalska; Laura Magdalena Sikorska; Paulina Pudło; Anna Koman; Martyna Bukowiec; Luiza Łabuzińska; Angela Ćwil; Mikołaj Asztabski; Kacper Byczek (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: The human skin microbiome is essential for maintaining skin homeostasis, modulating the immune response, and protecting against external threats. In recent years, researchers have increasingly focused on prebiotics and postbiotics bioactive chemicals that promote the proliferation of beneficial microorganisms or are produced by them as potential regulators of skin health. Although probiotics have attracted considerable interest as therapeutic agents, recent attention has focused on prebiotics, which selectively stimulate beneficial microbial populations, and postbiotics nonviable microbial products or metabolites with biological activity. Materials and Methods: This narrative review was based on an extensive analysis of the scientific literature published between 2010 and 2024. References were selected from sources such as PubMed, Scopus, and Google Scholar. The review focused on studies examining the mechanisms of action, clinical outcomes, and potential of prebiotics and postbiotics in the treatment or management of dermatological conditions. Results: The reviewed studies indicate that prebiotics and postbiotics can influence the skin microbiome by increasing microbial diversity, restoring barrier function, and reducing inflammatory responses. Evidence supports their effectiveness as supplements in the treatment of acne vulgaris, atopic dermatitis, psoriasis, and rosacea. Furthermore, their inclusion in cosmetic formulations appears to improve hydration, reduce transepidermal water loss, and enhance the skin’s innate defense mechanisms. Conclusions: Prebiotics and postbiotics represent a potential microbiome-targeted therapeutic approach to dermatological problems, both cosmetic and medical. Their incorporation into dermatological and cosmetological techniques may facilitate personalized, non-invasive, and preventative skin care approaches. However, additional, standardized, large-scale clinical trials are necessary to confirm their long-term safety and efficacy.